Status Hukum Harta Waris Berupa Tanah Hak Milik yang Menjadi Objek Perjanjian Nominee dalam Perspektif Hukum Waris, Hukum Perjanjian, dan Hukum Agraria - Muhammad Imamulhikmi; Susilowati Suparto; Kilkoda Agus Saleh (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Nominee agreements provide a way for foreigners to own land in Indonesia by using the name of an Indonesian citizen on the land certificate. The Indonesian citizen in the Nominee Agreement dies. The land used as an object in the Nominee Agreement is one of the inheritance assets to the legal heirs. The results showed that the disputed land should have fallen to the state, even though the heirs were legitimate heirs to inherit the property rights to the disputed land.